Assignment of near-edge x-ray absorption fine structure spectra of metalloporphyrins by means of time-dependent density-functional calculations - Schmidt, Norman Anja; Fink, Rainer; Hieringer, Wolfgang (Journal of Chemical Physics, 2010)
The C 1s and N 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of three prototype tetraphenyl porphyrin (TPP) molecules are discussed in the framework of a combined experimental and theoretical study. We employ time-dependent density-functional theory (TDDFT) to compute the NEXAFS spectra of the open- and closed-shell metalloporphyrins CoTPP and ZnTPP as well as the free-base 2HTPP in realistic nonplanar conformations. Using Becke's well-known half-and-half hybrid functional, the computed core excitation spectra are mostly in good agreement with the experimental data in the low-energy region below the appropriate ionization threshold. To make these calculations feasible, we apply a new, simple scheme based on TDDFT using a modified single-particle input spectrum. This scheme is very easy to implement in standard codes and allows one to compute core excitation spectra at a similar cost as ordinary UV/vis spectra even for larger molecules. We employ these calculations for a detailed assignment of the NEXAFS spectra including subtle shifts in certain peaks of the N 1s spectra, which depend on the central coordination of the TPP ligand. We furthermore assign the observed NEXAFS resonances to the individual molecular subunits of the investigated TPP molecules. © 2010 American Institute of Physics.